The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fimmu.2018.00976
|View full text |Cite
|
Sign up to set email alerts
|

VDJServer: A Cloud-Based Analysis Portal and Data Commons for Immune Repertoire Sequences and Rearrangements

Abstract: BackgroundRecent technological advances in immune repertoire sequencing have created tremendous potential for advancing our understanding of adaptive immune response dynamics in various states of health and disease. Immune repertoire sequencing produces large, highly complex data sets, however, which require specialized methods and software tools for their effective analysis and interpretation.ResultsVDJServer is a cloud-based analysis portal for immune repertoire sequence data that provide access to a suite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 66 publications
0
51
0
Order By: Relevance
“…The portal is accessible through a standard web browser via a user-friendly graphical user interface, which facilitates use by research groups that lack bioinformatics expertise. Moreover, VDJServer provides free access to High Performance Computing (HPC) at the Texas Advanced Computing Center (63).…”
Section: Vdjservermentioning
confidence: 99%
“…The portal is accessible through a standard web browser via a user-friendly graphical user interface, which facilitates use by research groups that lack bioinformatics expertise. Moreover, VDJServer provides free access to High Performance Computing (HPC) at the Texas Advanced Computing Center (63).…”
Section: Vdjservermentioning
confidence: 99%
“…The large numbers of antibody sequences now becoming available in the public domain raise the possibility of natural sequences being found that are identical to commercial sequences 5 . This is especially pertinent in the face of large-scale organized efforts to make naturally sourced antibody NGS data 8 and analytics 9,10 more accessible 11 . Specifically, we recently created the Observed Antibody Space (OAS) database that curates the NGS antibody data from public archives and makes them available for easy processing 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Some of these issues are addressed by services that provide Ig-seq-specific data deposition and analysis pipelines such as the B-T.CR wiki (https://b-t.cr), Imm-Port (http://immport.org) (26,27), immunoSEQ Analyzer (http:// clients.adaptivebiotech.com/), iReceptor (http://ireceptor.irmacs. sfu.ca/) (28), or VDJServer (http://vdjserver.org) (29). The iReceptor and the VDJServer are the main resources that fall under the umbrella of the organized effort of the Adaptive Immune Receptor Repertoire Community to provide standardized deposition and analysis pipelines for the Ig-seq outputs (24).…”
mentioning
confidence: 99%